Superficial Dorsal Vein Thrombosis of the Penis and Pulmonary Embolism in a 15-year-old Boy: A Case Report - Tomas Leng; Jason H. Homme; Jana Anderson (Clinical Practice and Cases in Emergency Medicine)
Introduction: Penile pain in children and adolescents is an uncommon presenting symptom in the emergency department (ED). The differential diagnosis includes trauma, priapism, urethral stone, infection, Mondor disease, Peyronie disease, and thrombosis. Case Report: A 15-year-old male with a high-risk, B-cell acute lymphocytic leukemia and recent pegaspargase administration presented to the ED with new-onset penile pain. After the administration of opioid analgesics, he developed hypoxia prompting an urgent computed tomography pulmonary angiogram that revealed bilateral segmental acute pulmonary embolism (PE). Ultrasound of the penis revealed findings consistent with superficial dorsal vein thrombosis of the penis. Conclusion: To our knowledge, this is the first case report of an adolescent with superficial dorsal vein thrombosis of the penis and a coexisting PE. Doppler ultrasound can provide a prompt assessment of penile induration and differentiate venous thrombosis from other causes.